Churchill walking with destiny - Roberts, Andrew 1963- (Allen Lane, an imprint of Penguin Books, 2018)
A magnificently fresh and unexpected biography of The Greatest Briton, by one of Britain's best-selling historians. Contains family tree of Churchill's extended family during his lifetime.
Keywords: Churchill, Winston -- 1874-1965; Churchill, Winston / 1874-1965; Prime ministers / Great Britain / Biography; Statesmen / Great Britain / Biography; Politicians / Great Britain / Biography; Great Britain / Politics and government / 20th century; Biografie